Pembuatan Sistem Informasi Akademik Paud Melati Harapan di Desa Sukaraja Kecamatan Sepaku Berbasis Web Menggunakan PHP dan MYSQL - kharisma aji aulia hapsari, kharisma aji aulia hapsari (JIMREK : Jurnal Ilmiah Rekayasa Elektro, 2025)
Early childhood education is a learning effort for children from birth to the age of six years which is carried out through the provision of educational stimuli to help physical and spiritual growth and development in order to have readiness to enter further education. Melati Harapan PAUD was established in 2006 which is located on Jl. Negara RT.16 KM 37 Sukaraja Village, Kec. Sepaku, Kab. PPU. This PAUD was established in collaboration with the Sukaraja village government through the village PKK with the local village community / self-help (private). PAUD Melati Harapan has several school data or report documents, such as student data and teacher data. However, so far there have been shortcomings in terms of data processing and how to convey information to parents as guardians of students, because PAUD Melati Harapan still uses a manual system. The purpose of making this research is to help parents of students in monitoring their children's grades and also make it easier for teachers to input data at PAUD Melati Harapan. This website is designed using PHP and Mysql, and this information system is connected to users who can provide information to users. In this study, a system has been created that has facilities such as student data, teacher data, class data, child grade data, child report cards, and lesson schedules.